The constitutionalization of the global corporate sphere - Thompson, Grahame (Oxford : Oxford University Press, 2013)
This work discusses governance, law, and constitutional matters in the context of international corporate constitutional governance. It examines how and why the business world commercial relations, and company activities have increasingly become subject to legal and constitutional forms of regulation and governance.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Corporation law; Corporate governance; International law; International organization; Globalization